2023
DOI: 10.3390/curroncol30020173
|View full text |Cite
|
Sign up to set email alerts
|

Risk Stratified Follow-Up for Endometrial Cancer: The Clinicians’ Perspective

Abstract: Risk-stratified follow-up for endometrial cancer (EC) is being introduced in many cancer centres; however, there appears to be diversity in the structure and availability of schemes across the UK. This study aimed to investigate clinicians’ and clinical specialist nurses’ (CNS) experiences of follow-up schemes for EC, including patient-initiated follow-up (PIFU), telephone follow-up (TFU) and clinician-led hospital follow-up (HFU). A mixed-methods study was conducted, consisting of an online questionnaire to C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…HCPs note that barriers to PIFU include patients' communication or language difficulties as well as a lack of technological developments to aid patient-clinician communication. 51 Some studies have shown that patients may not request urgent appointments despite recognising symptoms 52,53 and that regular FU can facilitate access to specialists or tests in these cases. 54,55 The reassurance regular FU can provide needs to be weighed against increased anxiety, the inconvenience of potentially unnecessary hospital visits and the fact that reassurance is often only temporary.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…HCPs note that barriers to PIFU include patients' communication or language difficulties as well as a lack of technological developments to aid patient-clinician communication. 51 Some studies have shown that patients may not request urgent appointments despite recognising symptoms 52,53 and that regular FU can facilitate access to specialists or tests in these cases. 54,55 The reassurance regular FU can provide needs to be weighed against increased anxiety, the inconvenience of potentially unnecessary hospital visits and the fact that reassurance is often only temporary.…”
Section: Discussionmentioning
confidence: 99%
“…Based on limited evidence, HCPs are generally supportive of PIFU, but have concerns about managing patient and HCP expectations, and about patients who have difficulties engaging with PIFU. HCPs note that barriers to PIFU include patients' communication or language difficulties as well as a lack of technological developments to aid patient–clinician communication 51 . Some studies have shown that patients may not request urgent appointments despite recognising symptoms 52,53 and that regular FU can facilitate access to specialists or tests in these cases 54,55 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations